REDUCING STUDENT ANXIETY THROUGH THE APPLICATION OF SPECIALIZED METHODOLOGY IN PHYSICAL EDUCATION CLASSES - V. Stoycheva (Trakia Journal of Sciences)
Anxiety is a common negative mental state. A major factor in its induction is high mental strain (distress). Students' learning activities are associated with varying degrees of tension, which in certain cases manifest as anxiety. It negatively affects their health and performance. One of the most effective means of reducing anxiety and limiting its negative impact is physical activity. Physical qualities are developed in physical education classes and physical exercise can have a positive impact on the psyche. Aim: to reduce students' anxiety by applying specialised methodology in physical education classes. Methods: Literature review, discussion, pedagogical experiment by applying complex impact methodology. The results were processed by variance analysis. Results: In the process of conducting regular physical education classes with the application of a specialized impact methodology, significantly decreased anxiety in students. Conclusions: Conditions are created to improve health and increase student success.